That's Not My Hamster.. - Annie Kubler (USA Usborne Publishing Ltd, 2012)
This is a delightful, brand new title in the award-winning "That's Not My..." series. You'll find hamsters with soft paws, squashy cheeks and a furry tummy, along with the familiar mouse inside this chunky board book. Rachel Well's colourful illustrations, along with the tactile touchy-feely patches have never-ending appeal for delight babies and toddlers. The textural patches and the descriptive words help to develop babies' and toddlers' sensory and language development.
Keywords: EY Libray Book ( EY - Wing ) -- EY Libray Book ( EY - Wing )